Simultaneous detection of Vibrio spp. in post-larvae stocking to harvest process of shrimps production in commercialised farms in Sarawak - Elexson, Nillian; Dalene, Lesenand; Nur Diyana, Zakaria (Malaysian Society for Microbiology, 2024)
Aims: The shrimp farming industry faces persistent challenges stemming from infectious diseases and environmental issues. The aim of this study was to monitor and assess the risk associated with the distribution of Vibrio spp. throughout the entire shrimp production cycle, spanning from the first day of culture (day 1) to the 98th day of culture (day 98). Methodology and results: The sampling was done by collecting water samples (n=48) and sediment samples (n=48) from three different locations: Telaga Air, Santubong and Tanjung Manis. Utilizing multiplex PCR with three specific primer sets, three Vibrio species were identified. Prevalence rates for V. parahaemolyticus were found to be 81.25% in water and 52.08% in sediment samples, while V. alginolyticus was detected in 16.67% of water samples and 27.08% of sediment samples. Vibrio cholerae was present in 10.42% of water samples and 25.0% of sediment samples. Furthermore, an antimicrobial susceptibility test (AST) was conducted on the Vibrio spp. isolates obtained from the three shrimp farms using 20 common antibiotics. Penicillin displayed the highest resistance rate at 40%, followed by streptomycin at 30%. The study also calculated the MAR index, which exhibited a range from 0.35 to 0.65. Conclusion, significance and impact of study: These research findings provide valuable insights into the distribution of Vibrio spp. in Sarawak aquaculture shrimp farms, which can help in preventing and controlling the possible occurrence of vibriosis.